2016
DOI: 10.1515/aiht-2016-67-2770
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meteorological parameters and air pollution on emergency department visits for cardiovascular diseases in the city of Zagreb, Croatia

Abstract: The aim of this study was to investigate whether nitrogen dioxide (NO2), ozone (O3), and certain meteorological conditions had an impact on cardiovascular disease (CVD)-related emergency department (ED) visits in the metropolitan area of Zagreb. This retrospective, ecological study included 20,228 patients with a cardiovascular disease as their primary diagnosis who were examined in the EDs of two Croatian University Hospitals, Sisters of Charity and Holy Spirit, in the study period July 2008-June 2010. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…However, if the exposure is decreased, IHD, arrhythmia and related diseases hospitalization costs could be diminished [25]. Our research, in which the monthly changes of CVD has a conjuncture structure, similar findings are obtained in the study by Pintaric et al [5] which was conducted in Croatia. Because there is a difference in higher estimations of admissions during winter and spring, our results may be due to increased air-pollutant concentration in Turkey.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, if the exposure is decreased, IHD, arrhythmia and related diseases hospitalization costs could be diminished [25]. Our research, in which the monthly changes of CVD has a conjuncture structure, similar findings are obtained in the study by Pintaric et al [5] which was conducted in Croatia. Because there is a difference in higher estimations of admissions during winter and spring, our results may be due to increased air-pollutant concentration in Turkey.…”
Section: Discussionsupporting
confidence: 88%
“…Epidemiological studies have shown the association between air pollution and climate change and health effects over the past decade. Many of these studies examined the effects of air pollution and climate change on daily mortality, emergency department visits, and hospital admissions for particularly cardiovascular and respiratory diseases in many parts of the world [1][2][3][4][5][6]. These studies provide evidence for the negative effects of urban air pollution on health and a better understanding of biological mechanisms; and in addition to creating an important field of research, they have allowed decision-makers to understand the effects of pollutants and the benefits that can be achieved by control measures [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining 17 studies, the majority utilized either a case-crossover design with conditional logistic regression [ 26 , 27 , 28 ], time series analysis utilizing Poisson regression [ 29 , 30 , 31 , 32 , 33 , 34 ], distributed lag nonlinear models [ 35 ], or generalized additive models [ 36 ]. Poisson regression and generalized linear regression [ 37 , 38 ], multiple stepwise regression analysis [ 39 ], canonical correlation analysis [ 40 ], and t -test [ 41 , 42 ] were also conducted. Detailed descriptions of the included studies can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The five systematic reviews included studies from North America, Europe, Asia, and Australia. Single studies were conducted in the United States [ 26 , 27 , 28 , 29 , 33 , 40 , 41 ], Canada [ 34 , 35 , 36 , 37 ], Southern Europe [ 31 , 38 , 39 ], Northern Europe [ 30 , 32 ], and Eastern Europe [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen dioxide is a primary pollutant and strong respiratory irritant mainly from outdoor sources including motor vehicles and fossilfuel power plants, whereas the most important indoor sources are gas heaters, stoves and tobacco smoke 28 . Th e number of patients admitted to ED correlates with the concentration of NO 2 and PM 10 particles 8,10,24,[29][30][31] , which have strong infl uence on cardiovascular morbidity and mortality. In this study, the number of patients with arrhythmias was in positive correlation with the concentration of NO 2 and PM 10 particles on the day of ED admission.…”
Section: Discussionmentioning
confidence: 99%